THE CONCEPT OF LIFE AND DEATH IN SURAH Al-MULK VERSE 2 AS A SOURCE OF VALUE FOR ISLAMIC EDUCATION FROM THE PERSPECTIVE OF TAFSIR AL-MUNIR BY WAHBA H AZ-ZUHAILI - Fathia Nurul izzah; Maulana Ibad; Ingka Wahyu Ningrum; Rabiatul Adawiyah Nasution; Fauziah Nur Ariza (Journal Informatic, Education and Management (JIEM), 2026)
This study explores the Islamic educational values contained in the concept of life and death as presented in Surah Al-Mulk verse 2 from the perspective of Tafsir Al-Munir by Wahbah az-Zuhaili. The study aims to analyze Wahbah az-Zuhaili’s interpretation of the verse and examine its relevance as a source of Islamic educational values. This research employs a qualitative approach using library research. The primary data source is Al-Tafsir Al-Munir fi al-‘Aqidah wa al-Shari’ah wa al-Manhaj, while secondary data are obtained from the Qur’an, Hadith, books, journal articles, and other relevant scholarly literature. Data were analyzed using the content analysis method. The findings indicate that life and death are Allah’s creations intended to test the quality of human deeds, where the measure of success is determined by sincerity of intention and conformity with Islamic teachings rather than the quantity of actions. Furthermore, Wahbah az-Zuhaili’s interpretation contains essential Islamic educational values, including faith education, moral education, spiritual education, character formation, responsibility, time discipline, and awareness of the ultimate purpose of human life as preparation for the Hereafter. These values serve as an important foundation for strengthening Islamic education in developing individuals with strong faith, noble character, and a lifelong commitment to righteous deeds.